The Misconception of Closed Magnetic Flux Lines - Zilberti, Luca (IEEE magnetics letters, 2017)
The belief that magnetic flux lines are always closed has been widely disseminated, handed down from Faraday through the present day. We review the problem and revisit the example of "the wire and the loop," which shows analytically that flux lines are not necessarily closed, and extend its analysis. The pictorial representation based on flux lines may give rise to erroneous conclusions not inherent in Maxwell's laws.